Método graus dia para avaliação do desempenho energético de uma edificação unifamiliar em diferentes condições climáticas. - Vendramin, Aurea Lúcia (2007)
The necessity of the application of climatic data for evaluation of energy performance in unifamiliares constructions if has become each more important time. Attempting against for this fact, one becomes necessary that these 0 variable are worked of form if to get resulted efficient. Studies in this area are very recent in Brazil and also exist a difficulty in the survey of the necessary registers. The present work used a method of degrees - days for an evaluation of the energy performance of a unifamiliar construction it showed - that in the conception of a project architectural it always must be taken in consideration of the materials used in the construction and size of the openings. The energy performance was gotten by means of the model of degrees - days, considering - the localization of the unifamiliar residence in, cities of Cascavel, Curitiba, Foz do Iguaçu and Londrina. For this the climatic data of such localities had been gotten and at as a moment, the energy performance of the construction was gotten the total coefficient of loss of heat in the unifamiliar construction daily pay-established evaluating thus the conditions of thermal comfort. The method of estimate based on the information of used temperature of air in this study can be applied to other geographic localities. It observed - that degrees - days of heating in the winter are of 77.78 for Curitiba and 0.00 for Foz do Iguaçu in the temperature base of 14°C. E degrees - days of cooling 30,17 in the winter. The energy consumed in Foz do Iguaçu to heat the residence is of 4650.07 kWh annual and the consumption of annual energy to heat the residence in Curitiba is of 6277.02 kWh, to change of 50% ITA in double glass.